UNDER THE BANNER OF VIOLENCE: HAMAS, AL-GAMAâ€™A AL-ISLAMIYYA, AND RADICAL ISLAMIC TERRORISM - Romaniuk, Scott Nicholas (European Scientific Journal, ESJ, 2014)
Examining the process by which religious and political groups undergo radicalization to a point where they eventually espouse the instrumentality of violence and terrorism for achieving their political objectives is a prevalent issue in the post-post-9/11 world, or in an era that might come to be known as the â€œ9/11-century.â€ This topic is timely and relevant in the context of religion and politics in the current geopolitical world given that we consistently see cyclical patterns of violent (Islamic) extremism, especially during times of crises, and in which members of entire demographic spectrums have become involved. This paper presents an examination of the religious radicalization of the highly ritualistic and extremely conservative Muslim group Hamas (Harakat Al-Muqawamah Al-Islamiyyah) or â€œThe Islamic Resistance Movementâ€ and former armed revolution group in Egypt during the 1970s and much of the 1990s Al-Gamaâ€™a Alâ€™Islamiyya (GAI). In doing so, it connects with the subjects of radicalization and deradicalization of such groups analyzing why some extremist groups eventually undergo a process of deradicalization while others do not. As one perspective commonly held among experts on terrorism and political violence underscores, terrorism is ultimately the product of parallel radicalization, and focuses on three groups; those of: victims, perpetrators, and bystanders (Baumeister, 1997; Miller, 1999; Staub, 1989). Thus, terrorism or asymmetric conflict and forms of political violence may be seen as the product of the interaction of multiple agents that consider their actions correct, a legitimate method of expressing discontent, and is consequently conducive to a vicious cycle of violence, aggression, and insecurity.